Studi Analisis Pergeseran Nilai Mahar Perkawinan Menurut Wahbah Al-Zuhaili - Fadilah Awaliyah; Jumni Nelli; Hendri Sayuti (Syntax Corporation Indonesia, 2024)
The objectives of this study To find out the forms of shifts in the value of marriage dowry in Indonesia. The type of research used in this study is library research, which is an effort to find and collect materials from book sources, research results and so on related to the research problem to be carried out, both in the form of an explanation of the research focus aspect (operational definition in qualitative terms), and to emphasize the position of the research to be carried out (standing position). As a result, there is a shift in the value of dowry in Indonesia, which was originally a symbol of love, affection, and respect for the future husband to the future wife. However, currently forms of dowry such as a glass of water, a cup of coffee, a bird, a crowbar, three chicken eggs, and flip-flops show a decline in value. An expensive gift that should be valuable, useful, and valuable becomes a gift that is worthless, has little benefit, and is not worth at all.